2017
DOI: 10.1063/1.4979016
|View full text |Cite|
|
Sign up to set email alerts
|

Driven similarity renormalization group: Third-order multireference perturbation theory

Abstract: A third-order multireference perturbation theory based on the driven similarity renormalization group approach (DSRG-MRPT3) is presented. The DSRG-MRPT3 method has several appealing features: a) it is intruder free, b) it is size consistent, pounds. This point is demonstrated with computations of the singlet-triplet splitting (∆ ST = E T − E S ) of 9,10-anthracyne. At the DSRG-MRPT3 level of theory, our best estimate of the adiabatic ∆ ST is 3.9 kcal mol −1 , a value that is within 0.1 kcal mol −1 from multire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 132 publications
(231 reference statements)
3
78
0
Order By: Relevance
“…The DSRG-MRPT2 error remains fairly constant (maximum value of 32.91 mE h ), and the resulting NPE is 18.4 mE h for N 2 /cc-pVDZ . Note that the DSRG-MRPT3 improves the description of the PES of 1 Σ g + N2 computed to DSRG-MRPT2 and yields a maximum deviation 13.88 mE h with an NPE equal to 4.80 mE h . , As per the work of Li–Evangelista, the deviations of CASPT2 and NEVPT2 results from FCI ones never exceed 22.87 and 34.17 mE h with NPEs 9.5 and 1.3 mE h . Analogous trends are also observed for the IVO-BWMRPT.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The DSRG-MRPT2 error remains fairly constant (maximum value of 32.91 mE h ), and the resulting NPE is 18.4 mE h for N 2 /cc-pVDZ . Note that the DSRG-MRPT3 improves the description of the PES of 1 Σ g + N2 computed to DSRG-MRPT2 and yields a maximum deviation 13.88 mE h with an NPE equal to 4.80 mE h . , As per the work of Li–Evangelista, the deviations of CASPT2 and NEVPT2 results from FCI ones never exceed 22.87 and 34.17 mE h with NPEs 9.5 and 1.3 mE h . Analogous trends are also observed for the IVO-BWMRPT.…”
Section: Resultsmentioning
confidence: 63%
“…As the above discussion illustrates that the IVO-BWMRPT is capable of tackling the complexity of C 2 rather well; next, we consider a demanding situation created by breaking of the triple bond in 1 Σ g + N 2 . ,,,,,,,,,, Note that CCSD and also CCSD­(T) provide an inadequate description of the bond breaking as it yields an unphysical hump on the energy surface at bond distances larger than the equilibrium one. ,, In our current study, six electrons in six orbitals, CAS­(6,6) [involving one σ and two π bonding orbitals as well as the corresponding antibonding orbitals, the smallest reasonable CAS] IVO-CASCI reference, have been used for N 2 as the dominant configuration changes from 3σ g 2 1π u 4 (excluding the first four occupied orbitals) near the equilibrium region to 3σ g 1 1π u 2 1π g 2 3σ u 1 in the dissociation region. Li and Paldus demonstrated that for larger N–N distances than about 1.5 R e ( R e designates the experimental equilibrium bond length, 2.068 a.u.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The equilibrium geometry of C 2 H 6 was taken from Ref. 60. In ppTDA@DFA, ppTDA@RS-DFA, CCSD calculations, the total energies at the bond length 5.0Å, 6.0Å, 4.0Å, 5.0A were set as zero for LiH, BH, CH + , C 2 H 4 respectively.…”
mentioning
confidence: 99%